2017
DOI: 10.1002/cbic.201600643
|View full text |Cite
|
Sign up to set email alerts
|

RNA Protection is Effectively Achieved by Pullulan Film Formation

Abstract: RNA is a functionally versatile polymer but suffers from susceptibility to spontaneous and RNase-catalyzed degradation. This vulnerability makes it difficult to preserve RNA for extended periods of time, thus limiting its use in various contexts, including practical applications as functional nucleic acids. Here we present a simple method to preserve RNA by pullulan (a complex sugar produced by Aureobasidium pullulans fungus) film formation. This strategy can markedly suppress both spontaneous and RNase degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…The inclusion of sugar molecules - pullulan and trehalose - in the bioink formulation is crucial for high functionally and stability of the printed paper sensor. As we have shown previously, these saccharides are able to prevent the denaturation of enzymes, degradation of labile small molecules, and hydrolysis of RNA species by auto-cleavage and RNase-induced degradation 13 , 31 , 39 .…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The inclusion of sugar molecules - pullulan and trehalose - in the bioink formulation is crucial for high functionally and stability of the printed paper sensor. As we have shown previously, these saccharides are able to prevent the denaturation of enzymes, degradation of labile small molecules, and hydrolysis of RNA species by auto-cleavage and RNase-induced degradation 13 , 31 , 39 .…”
Section: Discussionmentioning
confidence: 65%
“…Previous reports on RFD-EC1 have demonstrated that the DNAzyme is very specific for E. coli 26 , 38 , 39 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The use of urease and nucleic acids in the biosensor system makes this a relevant challenge. However, recently demonstrated methods that can stabilize proteins (Jahanshahi-Anbuhi et al, 2014 , 2016 ) and nucleic acids (including RNA-cleaving DNAzymes) (Hsieh et al, 2017 ) through the use of a natural polysaccharide known as pullulan have been reported. The same approach can be used to solve the issue of reagent stability of our system.…”
Section: Resultsmentioning
confidence: 99%
“…[19] Finally,w ee valuated the long-term stability of both aptamers on the paper sensor over ap eriod of 90 days when stored at 4 8 8C. [20] In conclusion, this work demonstrates that both fluorimetric and amplified colorimetric detection of targets is possible using aptamers printed onto paper devices with aconnecting bridge design. Interestingly,all of the loss in activity occurred in the first 10 days for both sensors.G iven the concordance between fluorescence and colorimetric data, it is most likely that instability occurs in Zone 1o wing to degradation of aptamers rather than instability of RCAr eagents in Zone 2.…”
mentioning
confidence: 76%